2020
DOI: 10.3390/ijms21031025
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis, Motility and Biofilm Formation Characteristics of Salmonella typhimurium Exposed to Benzyl Isothiocyanate Treatment

Abstract: Salmonella typhimurium (S. typhimurium) is a common foodborne pathogen that not only causes diseases and contaminates food, but also causes considerable economic losses. Therefore, it is necessary to find effective and feasible methods to control S. typhimurium. In this study, changes in S. typhimurium after treatment with benzyl isothiocyanate (BITC) were detected by transcriptomics to explore the antibacterial effect of BITC at subinhibitory concentration. The results showed that, in contrast to the control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 47 publications
(51 reference statements)
0
11
0
Order By: Relevance
“…Differentially expressed genes including down-and upregulated were noticed in BITC treated group in comparison to the control group [21]. Similarly, downregulated expression of virulence factors was also observed in BITC treated Staphylococcus aureus experimental group [22].…”
Section: Discussionmentioning
confidence: 63%
“…Differentially expressed genes including down-and upregulated were noticed in BITC treated group in comparison to the control group [21]. Similarly, downregulated expression of virulence factors was also observed in BITC treated Staphylococcus aureus experimental group [22].…”
Section: Discussionmentioning
confidence: 63%
“…SFN exhibited a stronger effect in this assay; however, PEITC at concentrations of 1 and 5 × MIC also affected biofilm formation. To date, the antibiofilm activity of ITC has been scarcely described in the literature, with some exceptions [ 33 , 34 , 35 ]; therefore, the molecular basis of its nature is poorly understood. Kaiser et al [ 23 ] showed that PEITC is effective in inhibiting P. aeruginosa biofilm formation even in concentrations significantly lower than the MIC (≤29 mg/mL).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the expression differences of pathogenicity-related genes in Salmonella typhimurium upon BITC treatment was explored using transcriptome analysis and phenotypic validation like motility and biofilm formation characteristics. Differentially expressed genes including down- and upregulated were noticed in BITC treated group in comparison to the control group [ 27 ]. Similarly, downregulated expression of virulence factors was also observed in BITC treated Staphylococcus aureus experimental group [ 28 ].…”
Section: Discussionmentioning
confidence: 99%